(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Right to Life is the most primordial of all rights as additionally the most transcendent. The plain first couplet of the Ramayan by Maharishi Valmiki embraces clearly and strongly the quintessence behind security everything being equal – man or creature alike. It is this Secure, safeguard and advance human life and its substance and doesn’t wreck it (or its pith) for once pulverized it can’t be reproduced. Each human body and psyche has an uprightness which is sacred. Each human being has sure final barest least needs, for example, right to air, consumable water, sustenance, apparel, wellbeing, therapeutic consideration and treatment, perfect and clean conditions for living convenience, environmental sanitation, individual cleanliness, etc. Hardship of any of these sums to viciousness to the individual. In this article we studied about the human rights, Laws for protecting the Disables, their treatment and other aspects.